Socioeconomic strain, crime and economic growth: evidence from Nigeria - Adekoya, Adenuga Fabian (2017)
Owing to the challenges posed by crime in Nigeria on citizenry and government financial plans and the implementation, this study explores criminal activities with the aim of seeing how the crime rate can be minimised in the country. Previous studies on crime in Nigeria have made a tremendous contribution to the crime literature, but they have not examined the association between socioeconomic strain and crime and the effect of crime on economic growth statistically. Thus, this study examines how socioeconomic strain factors contribute to the development of crime, and how crimes affect economic growth in Nigeria. Based on previous research, the link between socioeconomic strain, crime, and economic growth was explained via strain theory and rational choice theory. In testing the proposition of the theory, data from 1970 to 2013 were analysed with an autoregressive distributed lag (ARDL) model to examine the relationship while the modified Wald test approach to Granger causality was used to provide the causality direction. The results showed that socioeconomic strain affects crime positively, and crime affects economic growth negatively. Besides, the causality ran from socioeconomic strain to crime and from economic growth to crime against person. Based on the results, this study suggests that socioeconomic strain should be monitored and controlled, deterrence institutions should be strengthened, and vigorous policies for various investments should be well planned and implemented to reduce crime in Nigeria. This study believes that the policy that would check and reduce crime would improve economic growth.